PROSES KREATIF ANTONIUS WAHYUDI SUTRISNO SEBAGAI KOMPOSER GAMELAN - Ardi Gunawan; Danis Sugiyanto (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2014)
The creativity of Antonius Wahyudi Sutrisno (Dedek) in creating the composition be an interesting thing for the author to be further investigated. This research was focused on the factors behind Dedek in finding creative ideas. Dedek works based on tradition reiterates that he uses the idiom of tradition in his works. The idioms used a series of structures, motifs or patterns, and techniques. From the idiom invention, the author observed the tradition one, of such pathet space, instruments (gamelan), and a model of the work, which all is associated with the science of Javanese gamelan. Through pathet space, the author assume that Dedek has a unique in terms of the selection range of tones, although, that is uncommonly performed in tradition karawitan. The exploration of the instruments and methods in use in Dedek works, gamelan instruments perceived authors have character and distinctive characteristics. While on the model of Dedek composition is not far from the tradition of serving space and schema structure that resembles a traditional convention. This research reviewed the more clearly about the characters of the existing tradition in Dedek works that came from the tradition idioms.Keywords: creativity, karawitan composition, tradition idioms